Copy Number Variations in Genetic Diagnosis of Congenital Adrenal Hyperplasia Children - Tolba, Aisha; Mandour, Iman; Musa, Noha; Elmougy, Fatma; Hafez, Mona; Abdelatty, Sahar; Ibrahim, Amany; Soliman, Hend; Labib, Bahaaeldin; Elshiwy, Yasmine; Ramzy, Tarek; Elsharkawy, Marwa (Frontiers in Genetics, 2022)
Background: Congenital adrenal hyperplasia (CAH( is a monogenic disorder caused by genetic diversity in the CYP21A2 gene, with 21-hydroxylase deficiency (21-OHD) as the most common type. Early sex assignment and early diagnosis for different genetic variations with proper technique are important to reduce mortality and morbidity. Proper early sex identification reduces emotional, social and psychological stresses. Aim: Detection of a spectrum of aberrations in CYP21A2 gene including copy number variations, gene conversion, chimeric genes and point variations. Methods: The CYP21A2 gene was screened using MLPA assay in 112 unrelated Egyptian children with 21-OHD CAH (33 males and 79 females). Results: In the studied group, 79.5% were diagnosed within the first month of life, 46.8% of the genetic females were misdiagnosed as males. Among copy number variations results; large deletions in 15.4%, three types of chimeric genes in 9% (CH-1, CH-7, CAH-X CH-1) were detected. Regarding gene dosage one copy of CYP21A2 was found in 5 cases (4.5%), three copies were detected in 7 cases (6.3%) and one case (0.9%) showed four copies. Eight common genetic variants were identified; I2G, large deletions, large gene conversion (LGC), I172N, F306+T, -113 SNP, 8bp Del and exon 6 cluster (V237E, M239K) with allelic frequency of 32.62%, 15.45%, 7.30%, 3.00%, 2.58%, 2.15%, 0.86% and 0.86%, respectively. Conclusion: High prevalence of copy number variations highlights the added value of using MLPA in routine laboratory diagnosis CAH patients.